Procedural Formality, Substantive Reality: Evaluating Migrant Worker Protection in the Indonesia-Malaysia One Channel System (OCS) - Muhammad Alif Rifky; Anggia Utami Dewi; Wawan Budi Darmawan (Dinasti Publisher, 2025)
This research analyzes the effectiveness of the Indonesia-Malaysia cooperation in implementing the One Channel System (OCS) concerning the enhanced protection of Indonesian Migrant Workers (IMW) in the domestic sector. The primary issue investigated is the suboptimal substantive protection for IMW, despite the new policy framework established by the 2022 MoU. Using a qualitative research method involving policy document analysis and stakeholder interviews, this study examines the dynamics of OCS implementation. The findings indicate that the improvement in protection is more procedural, such as the legalization of tens of thousands of placements, rather than substantive progress, which relates to the improvement of workers’ real conditions. The effectiveness of OCS on the ground is undermined by three main factors: an asymmetry of national interests between Indonesia's focus on protection and Malaysia's orientation towards fulfilling labor demands; weak bilateral oversight and law enforcement mechanisms; and the continued operation of non-procedural recruitment channels by illegal brokers. This study recommends strengthening joint oversight institutions and enforcing strict law enforcement to bridge the gap between formal policy and on-the-ground reality.